Catalyst as well as preparation method and application thereof

By using sheet-like two-dimensional catalysts prepared by flexible materials, the existing low efficiency and difficult recovery problems of existing granular and powdery catalysts in applications are solved, achieving higher service life and lower costs.

CN119733557APending Publication Date: 2025-04-01NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311266082.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In actual applications, existing granular and powdered catalysts have problems such as low catalytic efficiency, difficult recycling, and high material waste and cost.

Method used

A two-dimensional catalyst is provided in a sheet-like manner, using a flexible material as a support, which has high tensile strength and corrosion resistance, and the active phase contains metal oxides of Group VIII, and the catalyst is prepared by injection molding and one-time molding.

Benefits of technology

It improves the service life and recovery rate of the catalyst, reduces the secondary pollution caused by metal loss, and reduces the overwater resistance of the catalyst, and improves the mass transfer efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733557A_ABST
    Figure CN119733557A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst as well as a preparation method and application thereof. The catalyst comprises a carrier and an active phase positioned on the carrier, the carrier has: a tensile strength in the range of 3.6 to 11.0 Mpa; the active phase comprises at least one metal oxide from the group VIII, and the amount of the metal oxide from the group VIII accounts for 5-20wt% of the total amount of the catalyst according to the weight percentage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and specifically relates to a catalyst and a preparation method and application thereof. Background Art

[0002] As one of the physicochemical treatment technologies, advanced oxidation treatment technology has the advantages of high treatment efficiency and more thorough destruction of toxic pollutants, and is widely used in the pretreatment process of toxic and difficult-to-degrade industrial wastewater. It has gradually become a hot spot in water treatment technology research. The current advanced oxidation technologies mainly include chemical oxidation, electrochemical oxidation, wet oxidation, supercritical water oxidation and photocatalytic oxidation. Taking chemical oxidation technology as an example, the chemical oxidation technology includes Fenton oxidation, Fenton-like oxidation, ozone oxidation, etc., which generally uses chemical oxidants to treat organic wastewater under the action of catalysts, and generates active free radicals with high oxidizing properties (·OH, ·O2 - , ·O, etc.) to remove refractory organic matter to improve the biodegradability of wastewater, or directly oxidize and degrade organic matter in wastewater to stabilize it. This type of technology usually has the advantages of rapid reaction, simple process, strong oxidation ability and easy reaction conditions. It is a high-efficiency and low-consumption sewage treatment technology with good development prospects in the field of sewage treatment. However, the existing chemical oxidation technology has problems such as low catalytic efficiency and difficulty in catalyst recovery, and the treatment effect still has a lot of room for improvement.

[0003] Taking ozone oxidation as an example, the existing catalytic ozone oxidation catalysts are mainly three-dimensional granular catalysts or powdered catalysts. Granular catalysts have a high specific surface area and are usually used in ozone fixed bed processes in a filling manner, but they have the defects of particle deposition and waste of catalytic performance of materials inside the particles. The reason is that the main sites of active free radicals are oxygen vacancies, Lewis acids and functional groups on the catalyst surface, while existing granular catalysts are usually spherical materials with a particle size of 3-5mm. The large particle size makes its internal structure unable to directly participate in catalysis. The large amount of internal structure not only reduces the volume density of active sites, but also leads to material waste and increased costs.

[0004] Compared with granular catalysts, powdered catalysts are as small as micro / nano levels, which can obtain higher specific surface area and increase the contact probability with catalysts / organic matter to break through the mass transfer bottleneck in low-concentration wastewater treatment. However, powdered catalysts require additional membrane separation and recovery processes, which are costly and complex to operate, and are difficult to apply. Therefore, they have the defect of large catalyst loss, which will also cause serious material waste and increased costs.

[0005] Therefore, existing granular and powdered catalysts have application bottlenecks that are difficult to overcome in practical applications, resulting in unsatisfactory actual use effects. Summary of the invention

[0006] 1. Problem to be solved

[0007] In view of the problem that existing granular catalysts or powdered catalysts are not good in practical use, the present invention aims to provide a sheet-like two-dimensional catalyst, which is easy to suspend and has low difficulty in separation and recovery;

[0008] At the same time, a method for preparing the catalyst is provided;

[0009] Furthermore, the provided catalyst is applied to water treatment.

[0010] 2. Technical solution

[0011] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0012] According to the purpose of the present invention, the catalyst provided in the first aspect of the present invention comprises:

[0013] a carrier, and an active phase on the carrier;

[0014] The carrier has: a tensile strength in the range of 3.6 to 11.0 MPa; and / or the carrier contains a high molecular polymer substance;

[0015] The active phase comprises at least one metal oxide from Group VIII. Calculated by weight, the amount of the metal oxide from Group VIII accounts for 5-20 wt % of the total amount of the catalyst.

[0016] It should be noted that for catalysts, the flexibility of their carriers is very important during use, such as when they are used in water treatment catalysis. During use, the integrity of the material can be well preserved, ensuring that the catalyst has good mechanical properties and structural stability, avoiding the powdering of the catalyst, and making separation and recovery more convenient; without being limited by theory, materials with a certain degree of flexibility will have better toughness and lower brittleness, and the probability of breakage during use will be lower. For example, the most typical traditional porous anodized transition metal template has a regular array of holes on its surface, and the material is extremely brittle. If it is used as a carrier to prepare a catalyst, it will be fragile during use and suffer great losses.

[0017] The present invention uses a "flexible material" containing a high molecular weight polymer as a carrier, so that the carrier has high plasticity, corrosion resistance and high temperature resistance. Therefore, the carrier in the catalyst of the present invention can effectively avoid the problem of easy corrosion of traditional metal carrier catalysts, effectively improve the service life of the catalyst and the recovery rate of the catalyst, and also reduce the secondary pollution caused by metal loss.

[0018] Preferably, the carrier has a tensile strength in the range of 4.5 to 9.0 MPa.

[0019] Further preferably, the carrier has a tensile strength in the range of 6.0 to 8.0 MPa.

[0020] According to any embodiment of the first aspect of the present invention, the carrier has an elongation at break in the range of 120 to 900%.

[0021] Preferably, the carrier has an elongation at break in the range of 120 to 500%.

[0022] Further preferably, the carrier has an elongation at break in the range of 120 to 250%.

[0023] According to any embodiment of the first aspect of the present invention, the carrier has a variation rate of elongation at break in the range of -20 to 20%.

[0024] Preferably, the carrier has a variation rate of elongation at break within a range of -13 to 13%.

[0025] Further preferably, the carrier has a change rate of elongation at break in the range of -10 to 10%.

[0026] According to any embodiment of the first aspect of the present invention, the carrier has a tear set in the range of 110 to 180%.

[0027] Preferably, the carrier has a tear set in the range of 110 to 150%.

[0028] Further preferably, the carrier has a tearing permanent deformation in the range of 110 to 130%.

[0029] According to any embodiment of the first aspect of the present invention, the carrier has a tensile strength variation rate in the range of -15 to 15%.

[0030] Preferably, the carrier has a tensile strength variation rate in the range of -10 to 10%.

[0031] Further preferably, the carrier has a tensile strength variation rate in the range of -7 to 7%.

[0032] According to any embodiment of the first aspect of the present invention, the amount of the metal oxide from Group VIII accounts for 8 to 15 wt% of the total amount of the catalyst;

[0033] Preferably, the amount of the metal oxide from Group VIII accounts for 8-10 wt% of the total amount of the catalyst.

[0034] According to any embodiment of the first aspect of the present invention, the carrier comprises a flexible material, and the flexible material is any one or two or more of silica gel, polyvinyl chloride plastic (PVC), and rubber.

[0035] According to any embodiment of the first aspect of the present invention, the carrier comprises a flexible material, and the amount of the flexible material accounts for 80 to 95 wt % of the total amount of the catalyst, calculated as a percentage by weight.

[0036] Preferably, the amount of the flexible material accounts for 85-92 wt % of the total amount of the catalyst.

[0037] Further preferably, the amount of the flexible material accounts for 90-92 wt % of the total amount of the catalyst.

[0038] According to any embodiment of the first aspect of the present invention, the carrier is provided with a through channel.

[0039] Compared with the traditional "whole sheet" two-dimensional catalyst, the catalyst carrier of the present invention can improve the water permeability of the catalyst by opening a through channel, reducing the water permeability resistance of the sheet structure of the two-dimensional catalyst. When the catalyst is impacted by water, the layered catalyst with water permeation holes can be more evenly suspended in the water, further improving the mass transfer efficiency of the catalyst.

[0040] According to any embodiment of the first aspect of the present invention, the carrier is a layered carrier, and a channel penetrating the thickness of the layered carrier is provided in the thickness of the layered carrier.

[0041] According to any embodiment of the first aspect of the present invention, the thickness H1 of the layered carrier is 200 to 800 μm;

[0042] Preferably, the thickness H1 is 200-600 μm;

[0043] More preferably, the thickness H1 is 200-400 μm.

[0044] According to any embodiment of the first aspect of the present invention, the active phase further comprises at least one adsorptive material, and the adsorptive material comprises any one or two or more of activated carbon, graphene, and zeolite molecular sieve.

[0045] According to any embodiment of the first aspect of the present invention, the active phase comprises at least one metal oxide particle from group VIII, the metal oxide particles having a particle size D, the particle size D being not less than the thickness H1.

[0046] Preferably, the particle size D is 250-450 μm.

[0047] According to any embodiment of the first aspect of the present invention, the active phase further comprises at least one adsorbent material powder, the adsorbent material powder being able to pass through a sieve of not less than 200 meshes;

[0048] Preferably, the adsorptive material powder can pass through a sieve of not less than 325 meshes.

[0049] According to any embodiment of the first aspect of the present invention, the catalyst comprises: a carrier, and an active phase located on the carrier; the carrier comprises silica gel, and the amount of the silica gel accounts for 75 to 90 wt % of the total amount of the catalyst.

[0050] According to any embodiment of the first aspect of the present invention, the catalyst comprises: a carrier, and an active phase located on the carrier; the carrier comprises silica gel, and the amount of the silica gel accounts for 80 to 87 wt % of the total amount of the catalyst.

[0051] According to any embodiment of the first aspect of the present invention, the catalyst comprises: a carrier, and an active phase located on the carrier; the carrier comprises silica gel, and the amount of the silica gel accounts for 85-87wt% of the total amount of the catalyst.

[0052] According to any embodiment of the first aspect of the present invention, the silicone rubber is an addition type liquid silicone rubber.

[0053] According to the purpose of the present invention, the second aspect of the present invention provides a method for preparing the catalyst, the method comprising the following steps:

[0054] preparing a liquid raw material, wherein the liquid raw material is a raw material for preparing the flexible material;

[0055] preparing a metal oxide feedstock from Group VIII;

[0056] Prepare catalyst curing and shaping mold;

[0057] The liquid raw material and the metal oxide raw material are injected into the mold and solidified.

[0058] The present invention adopts a one-step injection molding method to prepare the catalyst, which is different from the traditional method of first preparing the carrier material and then loading the active component on the carrier material. The method is convenient and simple to operate and is suitable for large-scale mass production.

[0059] According to any embodiment of the second aspect of the present invention, the present invention further comprises the following steps:

[0060] Prepare absorbent materials;

[0061] The adsorptive material, liquid raw material and metal oxide raw material are injected into the mold and solidified.

[0062] According to any embodiment of the second aspect of the present invention, the present invention further comprises the following steps:

[0063] Prepare absorbent materials;

[0064] First, inject the adsorbent material into the bottom of the mold,

[0065] Then, the liquid raw material and the metal oxide raw material are injected into the mold;

[0066] Finally, the adsorptive material is sprinkled on the surface of the "liquid raw material and metal oxide raw material in the mold".

[0067] According to any embodiment of the second aspect of the present invention, a plurality of protrusions are provided at the bottom of the mold; the protrusions are used to form channels penetrating the thickness of the catalyst in the thickness direction.

[0068] By controlling the shape, size, distribution density, etc. of the protrusions at the bottom of the mold, the layered catalyst can leave a water-passing "channel" for the intended purpose after solidification.

[0069] According to any embodiment of the second aspect of the present invention, the flexible material is silicone.

[0070] Prepare the raw materials for silica gel preparation: polydimethylsiloxane, methyl hydrogen silicone oil, and organic silicone resin (MQ silicone resin);

[0071] preparing a raw material powder of a metal oxide from Group VIII;

[0072] Prepare catalyst curing and shaping mold;

[0073] The silica gel preparation raw material and the metal oxide raw material powder are injected into the mold and cured and shaped.

[0074] According to any embodiment of the second aspect of the present invention, the mass ratio of the polydimethylsiloxane to the methyl hydrogen silicone oil is 100:(3-7);

[0075] Calculated based on the sum of the masses of the polydimethylsiloxane and the methyl hydrogen silicone oil;

[0076] The amount of the metal oxide raw material powder is 10wt% to 12wt% of the sum of the mass;

[0077] The amount of the organic silicon resin is 10 wt % to 30 wt % of the sum of the mass.

[0078] Based on the first aspect and / or the second aspect of the present invention, the third aspect of the present invention provides use of the catalyst in catalytic oxidation.

[0079] According to any embodiment of the third aspect of the present invention, the catalyst is used in catalytic ozone oxidation.

[0080] 3. Further explanation on the technical solution

[0081] Any embodiment of any aspect of the present invention can be combined with other embodiments without contradiction. In addition, in any embodiment of any aspect of the present invention, any technical feature can be applied to the technical feature in other embodiments without contradiction.

[0082] Under the premise that there is no contradiction, any technical feature of any aspect of the present invention or any embodiment of any aspect is also applicable to any other embodiment or any embodiment of any other aspect. Of course, when applicable to each other, the corresponding features can be appropriately modified if necessary. The various aspects and features of the present invention are further described below.

[0083] All documents cited in the present invention are incorporated herein by reference in their entirety, and if the meanings expressed in these documents are inconsistent with the present invention, the description of the present invention shall prevail. In addition, the various terms and phrases used in the present invention have the general meanings known to those skilled in the art. Even so, the present invention still hopes to provide a more detailed description and explanation of these terms and phrases. If the terms and phrases mentioned are inconsistent with the known meanings, the meanings expressed in the present invention shall prevail.

[0084] Unless otherwise indicated, it should be understood that each individual element in a list and each combination of individual elements in the list will be interpreted as a different embodiment. For example, a list of embodiments represented as "A, B, or C" should be interpreted to include embodiments "A", "B", "C", "A or B", "A or C", "B or C", or "A, B, or C".

[0085] In the present disclosure, the singular forms of the articles "a," "an," and "the" also include the corresponding plural references, and a reference to a specific value includes at least that specific value unless the context clearly indicates otherwise. Thus, for example, a reference to "a substance" is a reference to at least one of that substance and equivalents thereof.

[0086] The terms including ordinal numbers such as "first" and "second" can be used to explain various components or fluids, but these components and fluids are not limited by these terms. Therefore, without departing from the teachings of the present disclosure, these terms are only used to distinguish the component / fluid from another component / fluid.

[0087] When items are described by using the conjunction terms "... and / or...," etc., the description should be understood to include any one of the associated listed items and all combinations of one or more thereof.

[0088] In general, the use of the term "about" indicates an approximate value that may vary depending on the desired properties obtained by the disclosed subject matter, and will be interpreted in a context-dependent manner based on function. Therefore, one of ordinary skill in the art will be able to interpret a certain degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about". In other cases, a gradient in a range of values ​​can be used to determine the range of differences allowed by the term "about". Further, all ranges in this disclosure are inclusive and combinable, and reference to the values ​​stated in the range includes each value within the range.

[0089] In the present invention, the term "comprising" or "containing" means that various components can be used together in the composition of the present invention. Therefore, the terms "consisting mainly of" and "consisting of" are included in the terms "comprising" or "containing".

[0090] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the terms used herein and / or include any and all combinations of one or more of the associated listed items.

[0091] In order to demonstrate the technical solutions and advantages of the present invention, the technical solutions in the embodiments of the present invention will be fully described below.

[0092] The catalyst provided in the first aspect of the present invention comprises a carrier and an active phase located on the carrier.

[0093] As the "carrier", it is required to have a certain degree of tensile strength, such as a tensile strength of not less than 3Mpa; or, it is required to have a certain degree of elongation at break, such as an elongation at break of not less than 120%; or, it is required to have a certain degree of permanent deformation at break, such as a permanent deformation at break of not less than 110%; or, it is required to have a certain degree of tensile strength change rate, such as a tensile strength change rate of not less than -15; or, it is required to have a certain degree of change rate of elongation at break, such as a change rate of elongation at break of not less than -20.

[0094] Based on the above, in order to make the "carrier" meet any of the above requirements of "tensile strength", or "elongation at break", or "permanent deformation at break", or "tensile strength change rate", or "elongation at break change rate", a flexible material can be added to the carrier.

[0095] In the context of the present invention, the "flexible material" is mainly used to make the "carrier" have a certain tensile strength and / or deformation ability, and finally meet the flexibility, corrosion resistance and other requirements of the "carrier". Based on this, the flexible materials that can be listed are, for example, any one or two or more of silica gel, polyvinyl chloride plastic (PVC), and rubber; at this time, the amount of the flexible material is at least 80wt% of the total amount of the catalyst calculated by weight percentage.

[0096] As the "silicone" mentioned above, addition-type liquid silicone can be selected. The raw materials for preparing the formed liquid silicone are polydimethylsiloxane, methyl hydrogen silicone oil, and silicone resin; for example, the following can be cited:

[0097] The mass ratio of the polydimethylsiloxane to the methyl hydrogen silicone oil is 100:(3-7);

[0098] Calculated based on the sum of the masses of the polydimethylsiloxane and the methyl hydrogen silicone oil;

[0099] The amount of the organic silicon resin is 10 wt % to 30 wt % of the sum of the mass.

[0100] As the "polyvinyl chloride plastic" mentioned above, its raw materials for preparation are vinyl chloride, diisopropyl peroxydicarbonate, and polyvinyl alcohol; for example, the following can be cited:

[0101] The mass ratio of vinyl chloride to diisopropyl peroxydicarbonate is 100:5;

[0102] As the "rubber" mentioned above, its raw materials for preparation are butadiene and styrene; for example, the following can be cited:

[0103] The mass ratio of butadiene to styrene is 1:1.

[0104] In addition, in order to improve the suspension ability and separation ability of the catalyst during its application, the catalyst is required to be a two-dimensional (layered) catalyst. Therefore, the catalyst provided by the present invention has a layered carrier. On this basis, in order to further reduce the water resistance of the two-dimensional catalyst, the present invention has made further improvements to the two-dimensional metal catalyst, that is, holes that can be passed through the thickness layer of the catalyst are provided on the layered carrier of the catalyst, which are also called water "channels". The setting of the "channel" will make the two-dimensional catalyst provided by the present invention have good water permeability compared to traditional two-dimensional catalysts, reduce the water resistance of the layered structure, and when the catalyst is impacted by water inflow, it can reduce the impact load on the catalyst, ensuring that the layered structure of the "two-dimensional catalyst" can be more evenly suspended in water under the impact of water inflow and aeration, and further improve the mass transfer efficiency of the catalyst.

[0105] As the "channels" mentioned above, their density and size should be appropriately set to ensure that the layered structure has sufficient effective catalytic area to achieve efficient catalytic ozone oxidation. Specifically:

[0106] The size of the "channel" can be determined, for example, based on the specific area of ​​the "layered carrier". Taking the unit area of ​​the "layered carrier" as an example, the unit area is divided into six equal parts, and the shape of the "through-going channel" is the same as that of each of the equal parts, and the area is one-fourth of each of the equal parts.

[0107] The arrangement density of the "channels" per unit area of ​​the "layered carrier" can be specifically described as: dividing the unit area into six equal parts, and making a "through channel" with the center point of each part as the reference;

[0108] The thickness H1 of the "carrier" can be considered from the aspects of ensuring the lightness of the catalyst and reducing the fragility of the catalyst. Usually, too small a thickness increases the fragility of the catalyst, while too large a thickness affects the lightness of the catalyst, resulting in the catalyst failing to achieve the characteristic of being light due to the excessive thickness of the carrier layer, which is not conducive to suspension. Based on this, it is recommended that H1 can be arbitrarily selected within the range of 200 to 800 μm; for example, H1 can be 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, or 800 μm.

[0109] As the "active phase", one of its main functions is the "catalytic" performance; the "catalytic" performance, for example, can be catalyzing ozone oxidation to produce hydroxyl radicals, or catalyzing hydrogen peroxide to produce hydroxyl radicals; as the "active phase", its second main function is the "adsorption" performance.

[0110] Based on the requirement of the "catalytic" performance, the "active phase" contains at least one metal oxide from Group VIII, for example, any one or two or more of iron (Fe), cobalt (Co), nickel (Ni), etc.

[0111] In addition, considering the effect on the catalytic activity, calculated by weight, the amount of the metal oxide from Group VIII accounts for at least 5wt% of the total amount of the catalyst; for example, calculated by weight, the amount of the metal oxide from Group VIII accounts for 5-20wt%, 5-15wt%, 5-10wt%, 8-20wt%, 8-15wt%, 8-10wt%, 10-20wt%, 10-15wt% of the total amount of the catalyst.

[0112] The "Group VIII metal oxide" is added in the form of powder, and after being added, it will be in the catalyst in the form of "particles" as the final form.

[0113] As described herein, "particles" include "single metal oxide particles" or "agglomerates of a number of metal oxide particles formed by various forces". Regarding the particle size D of the "particles", it is recommended that its size is not less than the thickness H1 of the "carrier". The reason is to ensure that the "particles" can be "exposed" as much as possible on the surface of the layered "carrier" so that the catalyst has more catalytic active sites. Based on this, for example, when the thickness H1 of the "carrier" is selected from a specific value in the range of 200 to 800 μm, the particle size D of the "particles" at least meets the conditions: 200 microns ≤ D < 900 microns, and, at the same time, H1 ≤ D needs to be satisfied.

[0114] As the "Group VIII metal oxide particles", part of them is present in the layered "carrier" in an embedded manner. Further, the amount of the part accounts for no less than 50% of the total amount; preferably, the amount of the part accounts for no less than 70% of the total amount; further preferably, the amount of the part accounts for no less than 90% of the total amount; most ideally, the amount of the part accounts for 100% of the total amount.

[0115] Based on the requirement of the "adsorption" performance, as the "active phase", it contains at least one adsorptive material, for example, any one or two or more of activated carbon, graphene, and zeolite molecular sieves. The adsorptive material is mainly distributed on the surface of the layered "carrier" of the "catalyst". Based on this, the adsorptive material is required to be in powder form, and the "powder" can, for example, pass through a sieve of not less than 200 meshes.

[0116] The second aspect of the present invention provides a method for preparing the catalyst; comprising steps (A) to (C), (F), and (H); preferably, steps (D) and (E) are further included before step (F), step (G) is further included between steps (F) and (H), and step (I) is further included after step (H). The operation sequence of the steps is as follows:

[0117] Sorting 1: (A) to (D), wherein there is no mandatory order for steps (A) to (D):

[0118] Sort 2: (E);

[0119] Sort 3: (F);

[0120] Sort 4: (G);

[0121] Sort 5: (H);

[0122] Sort six: (I).

[0123] Regarding the step (A): preparing a liquid raw material, wherein the liquid raw material is a raw material for preparing the flexible material;

[0124] The “flexible material” mentioned above may include, for example, any one or two or more of silicone, polyvinyl chloride (PVC), and rubber.

[0125] When the "flexible material" is "silicone", addition-type liquid silicone can be selected, and the raw materials for preparing the formed liquid silicone are polydimethylsiloxane, methyl hydrogen-containing silicone oil, and silicone resin; as the polydimethylsiloxane, its viscosity (25℃cp) is 500~5000; as the methyl hydrogen-containing silicone oil, it is preferably a linear methyl hydrogen-containing silicone oil with a viscosity of (25℃cp) 15~50.

[0126] The mass ratio of the polydimethylsiloxane to the methyl hydrogen silicone oil is 100:(3-7);

[0127] Calculated based on the sum of the masses of the polydimethylsiloxane and the methyl hydrogen silicone oil;

[0128] The amount of the metal oxide raw material is 10wt% to 12wt% of the sum of the mass;

[0129] The amount of the organic silicon resin is 10 wt % to 30 wt % of the sum of the mass.

[0130] When the "flexible material" is "polyvinyl chloride plastic", its raw materials are vinyl chloride, diisopropyl peroxydicarbonate, and polyvinyl alcohol;

[0131] The mass ratio of vinyl chloride to diisopropyl peroxydicarbonate is 100:5;

[0132] Calculated based on the sum of the masses of vinyl chloride and diisopropyl peroxydicarbonate;

[0133] The amount of the metal oxide raw material is 10wt% to 12wt% of the sum of the mass;

[0134] When the "flexible material" is "rubber", its raw materials are butadiene and styrene;

[0135] The mass ratio of butadiene to styrene is 1:1;

[0136] Calculated based on the sum of the masses of butadiene and styrene;

[0137] The amount of the metal oxide raw material is 10 wt% to 12 wt% of the sum of the masses.

[0138] In this step, "silicone" is preferably used as the "flexible material", especially addition-type liquid silicone, which is a high molecular polymer material with corrosion resistance and high temperature resistance. Therefore, the catalyst with silica gel as the carrier avoids the problem of easy corrosion of metal in metal carrier catalyst, can effectively improve the service life of the catalyst and the recovery rate of the catalyst, and also reduces the secondary pollution caused by metal loss.

[0139] Regarding the step (B): preparing a metal oxide raw material from Group VIII;

[0140] The “Group VIII metal oxide raw material” is used in a powder form.

[0141] Regarding the step (C): preparing a catalyst curing and shaping mold;

[0142] The focus of the "mold" used for catalyst curing and shaping is the design of the bottom. A number of protrusions are provided at the bottom of the mold. The height, shape and size of the protrusions are set according to the specific requirements of the water-passing "channel" to be present on the desired catalyst and the thickness of the catalyst (or its carrier), so as to form a water-passing "channel" that runs through the thickness of the catalyst in the thickness direction.

[0143] Regarding the step (D): preparing an adsorbent material;

[0144] There are no special requirements for the selection of the "adsorbent material", for example, any one or two or more of activated carbon, graphene, and zeolite molecular sieves can be cited; as for the form of the "adsorbent material", it is preferred to select powder particles processed into the required particle size, for example, the adsorbent material powder can pass through a sieve of not less than 200 mesh.

[0145] Regarding the step (E): dispersing the adsorptive material in the mold;

[0146] At the bottom of the mold, a layer of 200-mesh adsorptive material powder is spread as evenly as possible. There is no mandatory requirement for the thickness of the adsorptive material powder at the bottom of the mold, for example, it can be 100-150 μm. However, since the excess adsorptive material on the surface of the flexible carrier needs to be washed off after curing, the thickness of the adsorptive material adsorbed on the surface of the carrier is not equal to the thickness spread on the bottom of the mold. The specific thickness of the adsorptive material adsorbed on the surface of the carrier is related to the amount of liquid silicone and the particle size of the adsorptive material.

[0147] Regarding the step (F): injecting the liquid raw material and the metal oxide raw material into the mold;

[0148] In the present invention, before carrying out step (F), the operation is usually: firstly, the liquid in step (A) is Raw materials and steps The metal oxide powders in (B) are mixed to form a mixture containing both and mixed as evenly as possible;

[0149] The mixture containing the "liquid raw material and metal oxide powder" is slowly injected into the mold, and the injection is stopped when the thickness of the mixture in the mold reaches a predetermined target.

[0150] It should be noted here that, during the preparation process of the "two-dimensional catalyst", the present invention discovered that the "metal oxide powder" also has the function of catalyzing the solidification of the "liquid raw material"; and the amount of "metal oxide powder" added in the present invention exceeds the amount required to catalyze the solidification of the "liquid raw material", which can make the final formed catalyst have higher (ozone, hydrogen peroxide, etc.) catalytic activity, and can also ensure that the "Group VIII metal oxide particles" are exposed to the catalyst surface to the greatest extent.

[0151] That is to say, in fact, the "Group VIII metal oxide powder / particles" have both the solidification catalytic effect of the "liquid raw material" in the catalyst preparation process and the role of the "catalytically active component" in the catalyst application process.

[0152] Regarding the step (G): dispersing the adsorptive material on the surface of the “liquid raw material and metal oxide raw material”;

[0153] After the injection of the mixture stops, a layer of adsorptive material powder is spread on the surface of the mixture. There is no mandatory requirement for the spreading thickness of the adsorptive material powder, for example, it can be 100-150 μm. However, since the excess adsorptive material on the surface of the flexible carrier needs to be washed off after curing, the thickness of the adsorptive material adsorbed on the surface of the carrier is not equal to the thickness spread on the surface of the mixture. The specific thickness of the adsorptive material adsorbed on the surface of the carrier is related to the amount of liquid silicone and the particle size of the adsorptive material.

[0154] Regarding the step (H): curing and shaping;

[0155] There is no particular requirement for the method of "curing and setting", and the curing and setting can be carried out by existing methods, such as drying in an oven, natural drying in a natural state, etc.

[0156] A typical operation for reference is: put the mold into a constant temperature box at 50-80℃ for curing for 15-60 minutes, and after curing, take out the mold and cool it to room temperature.

[0157] Regarding the step (I): after the catalyst is demoulded and taken out from the mold, both sides of the catalyst are rinsed with deionized water to obtain a finished product.

[0158] In a third aspect of the present invention, the catalyst is used for catalytic ozone oxidation to carry out water treatment.

[0159] Instruction Manual

[0160] Figure 1 This is a structural diagram of a mold for preparing a catalyst according to Examples 1-3 of the present invention;

[0161] Figure 2 The structure diagram of the catalyst (front view) of Example 1-3 of the present invention;

[0162] Figure 3 The structure diagram of the catalyst (side view) of Example 1-3 of the present invention;

[0163] Figure 4-1 This is a physical picture of the catalyst prepared in Example 1 of the present invention;

[0164] Figure 4-2 This is a physical picture of the catalyst prepared in Example 1 of the present invention (bent state);

[0165] Figure 5 This is a SEM image of the catalyst of Example 1 of the present invention;

[0166] Figure 6-1 This is the EDS image of the catalyst of Example 1 of the present invention;

[0167] Figure 6-2This is the EDS image of the catalyst of Example 1 of the present invention;

[0168] Figure 6-3 This is the EDS image of the catalyst of Example 1 of the present invention;

[0169] Figure 7-1 A water flow demonstration diagram of the catalyst (with a water flow channel) prepared in Example 1-3 of the present invention;

[0170] Figure 7-2 This is a water flow demonstration diagram of the two-dimensional catalyst (without a water flow channel) prepared in Example 4 of the present invention;

[0171] Figure 8 The catalytic effect diagram of the catalyst prepared in Examples 1-3 of the present invention;

[0172] Fig. 9 The catalytic effect diagram of the catalyst prepared in Examples 3 and 4 of the present invention;

[0173] Fig.10 The catalytic effect diagram of the catalyst prepared in Examples 3 and 5 of the present invention;

[0174] Fig.11 The catalyst prepared in Examples 1-5 of the present invention is shown in the recovery mass diagram;

[0175] In the figure: 100, convex points of the mold; 200, catalyst (with a channel for water to flow); 210, channel; 220, activated carbon powder; 230, carrier; 300, water flow direction; 400 ozone; 500, catalyst (without a channel for water to flow). DETAILED DESCRIPTION

[0176] The present disclosure may be more easily understood by reference to the following description in conjunction with the accompanying drawings and examples, all of which constitute a part of the present disclosure. It should be understood that the present disclosure is not limited to the specific products, methods, conditions or parameters described and / or shown herein. Further, the terms used herein are only used for the purpose of describing specific embodiments by way of example and are not intended to be limiting unless otherwise stated.

[0177] It should also be understood that, for the sake of clarity, certain features of the present disclosure may be described herein in the context of separate embodiments, but may also be provided in combination with each other in a single embodiment. That is, unless clearly incompatible or specifically not included, each separate embodiment is considered to be combinable with any other embodiment, and the combination is considered to represent another different embodiment. Conversely, for the sake of simplicity, the various features of the present disclosure described in the context of a single embodiment may also be provided individually or in any sub-combination. Finally, although a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure itself may also be considered to be an independent embodiment.

[0178] Example 1

[0179] The catalyst provided in this embodiment includes a carrier and an active phase located on the carrier;

[0180] The carrier contains nearly 100 wt % of a flexible material, and the flexible material is an addition-type liquid silicone rubber;

[0181] The carrier is a layered carrier, the thickness H1 of the layered carrier is 200 μm, and a channel with a rectangular cross section is opened on it. The position and size of the channel are described as dividing the layered carrier into six equal parts. The position of the channel is based on the center of each part, and the size is 1 / 4 of the area of ​​each part. In this example, the specific cross-sectional area of ​​the channel is 0.5 cm 2 (1 cm × 0.5 cm), the distribution density of the channels on the layered carrier is every 2 cm 2 Set up a channel;

[0182] In addition, the carrier satisfies the following characteristics:

[0183] Tensile strength not less than 6.0Mpa;

[0184] The tensile strength change rate is not less than 3%;

[0185] Elongation at break not less than 180%;

[0186] The tearing permanent deformation is not less than 130%;

[0187] The change in elongation at break is not less than 5%.

[0188] The active phase includes oxide CoO powder / particles of metal Co from group VIII (the particle size D is larger than the thickness of the layered support, and the specific size of the particle size D is 230-260 μm) and activated carbon powder (passing through a 200 mesh sieve);

[0189] Calculated by weight percentage, the oxide of the metal Co from Group VIII accounts for 8.3 wt % of the total amount of the catalyst.

[0190] This embodiment provides a method for preparing the catalyst product as described above:

[0191] This example is implemented according to the ratio (by weight) of polydimethylsiloxane and linear methyl hydrogen silicone oil of 100:3, the amount of catalyst is 10% of the total amount of polydimethylsiloxane and linear methyl hydrogen silicone oil, and the amount of filler MQ silicone resin is 10% of the total amount of polydimethylsiloxane and linear methyl hydrogen silicone oil. The specific steps are as follows:

[0192] Step 1: Select polydimethylsiloxane with a viscosity (25℃cp) of 1000, linear methyl hydrogen silicone oil with a viscosity of 20, MQ silicone resin and CoO powder as raw materials for synthesizing silica gel carrier.

[0193] Step 2: Dispense the base materials into corresponding containers and add them into the mixer according to the amount through the metering system. Among them, take 100g of polydimethylsiloxane, 3g of linear methyl hydrogen silicone oil, 10.3g of CoO powder, and 10.3g of filler MQ silicone resin.

[0194] Step 3: Figure 1 At the bottom of the mold shown, a layer of 200-mesh powdered activated carbon is laid, and then the raw materials are quickly mixed in the mixer and slowly pumped into the mold. After the thickness of the liquid raw material reaches 200μm, another layer of 200-mesh powdered activated carbon is laid on the surface of the raw material. The thickness of the activated carbon laid on the bottom of the mold and the surface of the raw material is a thin layer of 120μm, but the thickness of the activated carbon layer finally attached to the surface of the carrier is between 74 and 120μm (the particle size of 200-mesh powdered activated carbon is 74μm)

[0195] Step 4: Place the mold in a constant temperature box at 60°C for curing for 20 minutes. After curing, take out the mold and cool it to room temperature.

[0196] Step 5: After the layered catalyst is demoulded and taken out from the mold, both sides of the catalyst are rinsed with deionized water to remove the excess powdered activated carbon to obtain the finished product as described above. The finished product has the following characteristics: Figure 2 The channels shown in FIG. 1 and FIG. 2 for water to pass through the thickness of the support, and the channels shown in FIG. Figure 3 The layer structure shown in FIG. 1 is a layer structure shown in FIG. 1 ; the final object is as shown in FIG. Figure 4-1 As shown, and as Figure 4-2 As shown, it has excellent flexibility.

[0197] like Figure 5As shown in FIG. 1 , it is a SEM image of the finished product. It can be seen from the image that the oxide particles of the Group VIII metal cobalt (Co) of the catalyst are perfectly embedded in the silica gel carrier. It can also be seen from the image that the size of the catalyst metal oxide particles is basically between 200 and 300 μm, and the particle size is slightly larger than the silica gel carrier sheet (200 μm), so it is ensured that the catalyst can be exposed on the carrier surface without being completely covered by the silica gel.

[0198] like Figure 6-1 As shown, it is the EDS image of the finished product, from which it can be seen that carbon (C) is evenly distributed on the catalyst surface, which comes from the powdered activated carbon layer finally loaded on the catalyst surface;

[0199] like Figure 6-2 and 6-3 As shown, it is the EDS image of the finished product, from which it can be seen that cobalt oxide (CoO) is embedded in the catalyst, and the agglomerated Co element and O element correspond to the cobalt oxide (CoO) particles in the SEM image, while the small amount of dispersed Co element may be caused by the shedding of some Co particles generated during the preparation process;

[0200] Step 6: Using a total mass of 5g of the prepared flexible layered catalyst, an ozone catalytic oxidation experiment was carried out. The target pollutant was oxalic acid, so as to examine the performance of the catalyst in catalyzing ozone oxidation and degradation of organic matter.

[0201] In this embodiment, the initial concentration of oxalic acid is 100 mg / L, the volume is 200 ml; the ozone concentration is 5 mg / L, the flow rate is 0.5 L / min; and the reaction time is 15 min.

[0202] Example 2

[0203] In this example, the ratio (by weight) of polydimethylsiloxane and linear methyl hydrogen silicone oil is 100:5, the amount of catalyst is 11% of the total amount of polydimethylsiloxane and linear methyl hydrogen silicone oil, and the amount of filler MQ silicone resin is 20% of the total amount of polydimethylsiloxane and linear methyl hydrogen silicone oil.

[0204] Step 1: Select polydimethylsiloxane with a viscosity (25℃cp) of 3000, linear methyl hydrogen silicone oil with a viscosity of 30, MQ silicone resin and CoO powder as raw materials for synthesizing silica gel carrier.

[0205] Step 2: Dispense the base materials into corresponding containers and add them into the mixer according to the amount through the metering system. Among them, take 100g of polydimethylsiloxane, 5g of linear methyl hydrogen silicone oil, 11.6g of CoO, and 21g of filler MQ silicone resin.

[0206] Step 3: Spread a layer of 200-mesh powdered activated carbon on the bottom of the mold, then quickly mix the raw materials in the mixer and slowly pump them into the mold. When the thickness of the liquid raw material reaches 300μm, spread another layer of 200-mesh powdered activated carbon on the surface of the raw material. The thickness of the activated carbon laid on the bottom of the mold and the surface of the raw material is a thin layer of 120μm, but the thickness of the activated carbon layer finally attached to the surface of the carrier is between 74 and 120μm (the particle size of 200-mesh powdered activated carbon is 74μm)

[0207] Step 4: Place the mold in a constant temperature box at 80°C for 15 minutes to cure. After curing, take out the mold and cool it to room temperature.

[0208] Step 5: After removing the layered catalyst from the mold, rinse both sides of the catalyst with deionized water to wash away excess powdered activated carbon to obtain the finished product.

[0209] Step 6: Using a total mass of 5g of the prepared flexible layered catalyst, an ozone catalytic oxidation experiment was carried out. The target pollutant was oxalic acid, so as to examine the performance of the catalyst in catalyzing ozone oxidation and degradation of organic matter.

[0210] In this embodiment, the initial concentration of oxalic acid is 100 mg / L, the volume is 200 ml; the ozone concentration is 5 mg / L, the flow rate is 0.5 L / min; and the reaction time is 15 min.

[0211] Example 3

[0212] In this example, the ratio (by weight) of polydimethylsiloxane and linear methyl hydrogen silicone oil is 100:7, the amount of catalyst is 12% of the total amount of polydimethylsiloxane and linear methyl hydrogen silicone oil, and the amount of filler MQ silicone resin is 30% of the total amount of polydimethylsiloxane and linear methyl hydrogen silicone oil.

[0213] Step 1: Select polydimethylsiloxane with a viscosity (25℃cp) of 5000, linear methyl hydrogen silicone oil with a viscosity of 40, MQ silicone resin and CoO powder as raw materials for synthesizing silica gel carrier.

[0214] Step 2: Dispense the base materials into corresponding containers and add them into the mixer according to the amount through the metering system. Among them, take 100g of polydimethylsiloxane, 7g of linear methyl hydrogen silicone oil, 12.8g of CoO, and 32.1g of filler MQ silicone resin.

[0215] Step 3: Spread a layer of 325 mesh powdered activated carbon on the bottom of the mold, then quickly mix the raw materials in the mixer and slowly pump them into the mold. When the thickness of the liquid raw material reaches 400μm, spread another layer of 325 mesh powdered activated carbon on the surface of the raw material. The thickness of the activated carbon laid on the bottom of the mold and the surface of the raw material is a thin layer of 120μm, but the thickness of the activated carbon layer finally attached to the surface of the carrier is between 45 and 120μm (the particle size of 325 mesh powdered activated carbon is 45μm)

[0216] Step 4: Place the mold in a constant temperature box at 100°C for 10 minutes. After curing, take out the mold and cool it to room temperature.

[0217] Step 5: After removing the layered catalyst from the mold, rinse both sides of the catalyst with deionized water to wash away excess powdered activated carbon to obtain the finished product.

[0218] Step 6: Using a total mass of 5g of the prepared flexible layered catalyst, an ozone catalytic oxidation experiment was carried out. The target pollutant was oxalic acid, so as to examine the performance of the catalyst in catalyzing ozone oxidation and degradation of organic matter.

[0219] In this embodiment, the initial concentration of oxalic acid is 100 mg / L, the volume is 200 ml; the ozone concentration is 5 mg / L, the flow rate is 0.5 L / min; and the reaction time is 15 min.

[0220] Example 4

[0221] This embodiment is basically the same as Embodiment 3; the only difference is the design of the convex points of the mold:

[0222] The mold described in this embodiment does not have protrusions. Based on this, the layered catalyst prepared in this embodiment does not have water holes.

[0223] In this example, an ozone catalytic oxidation experiment was also carried out with a total mass of 5 g of the prepared flexible layered catalyst. The specific experimental conditions were the same as those in Example 3, so as to examine the performance of the catalyst in catalyzing ozone oxidation to degrade organic matter.

[0224] Example 5

[0225] This embodiment is basically the same as embodiment 3; the only difference is the use of powdered activated carbon:

[0226] In step 3: do not spread a layer of 325-mesh powdered activated carbon on the bottom of the mold. Instead, the raw materials are quickly mixed in the mixer and then slowly pumped into the mold. After the thickness of the liquid raw material reaches 400μm, no more layer of 325-mesh powdered activated carbon is spread on the surface of the raw material.

[0227] Based on this, the layered catalyst prepared in this example does not contain activated carbon powder.

[0228] In this example, an ozone catalytic oxidation experiment was also carried out with a total mass of 5 g of the prepared flexible layered catalyst. The specific experimental conditions were the same as those in Example 3, so as to examine the performance of the catalyst in catalyzing ozone oxidation to degrade organic matter.

[0229] Comparative Example 1

[0230] Preparation of two-dimensional catalysts based on aluminum.

[0231] Step 1: Select several aluminum foil sheets with a thickness of 200 μm, pre-treat the surface of the aluminum foil sheets by degreasing, grinding, brushing, washing, etc., and then dry them in an oven at 50°C after pre-treatment.

[0232] Step 2: Weigh 50g of oxalic acid dihydrate at room temperature, add clean water (such as deionized water) to prepare 1L of 50g / L oxalic acid solution, take 300ml of oxalic acid solution as the corrosion electrolyte, place the reaction container containing the corrosion electrolyte in an ice water bath, and keep the temperature at 10±1℃.

[0233] Step 3: Use the titanium plate as the cathode and the aluminum foil pretreated in step 1 as the anode. The electrode spacing is 2 cm. Anodization is performed at a voltage of 60 V for 12 hours. After the reaction, the two-dimensional foil is cleaned and stored in clean water (such as deionized water).

[0234] Step 4: Take out the two-dimensional material stored in step 3 and dry it in an oven at 50°C for 12 hours.

[0235] Step 5: Prepare 500 ml of 8 wt% phosphoric acid solution at room temperature, and immerse the dried two-dimensional material in the phosphoric acid solution kept at a constant temperature of 35° C. in an oven for 60 minutes to make the two-dimensional foil flexible. Then, wash the two-dimensional material with clean water (such as deionized water) and dry it in an oven at 50° C.

[0236] Step 6: At room temperature, weigh 3 g of glucose, 0.5 g of nickel chloride, 1 g of copper nitrate, and 3 g of cobalt acetate and add 100 ml of clean water (such as deionized water) to prepare a precursor solution.

[0237] Step 7: Vacuum impregnate the flexible and dried two-dimensional foil in the above solution. During the impregnation process, the precursor salt will synchronously corrode the two-dimensional carrier. After sufficient impregnation and synchronous completion of the corrosion load, the two-dimensional foil is left to stand at room temperature for 15 hours to allow the precursor to fully diffuse, and then placed in a 70°C vacuum oven for drying and pre-pyrolysis for 15 hours.

[0238] Step 8: Place the dried two-dimensional foil in an argon protection furnace, heat up at a rate of 3°C / min, heat to 350°C, keep warm for 1.5 hours, then cool to room temperature at a rate of 3°C / min to obtain the finished product.

[0239] Step 9: Using a total mass of 5g of the prepared two-dimensional catalyst, an ozone catalytic oxidation experiment was carried out. The target pollutant was oxalic acid, so as to examine the performance of the catalyst in catalyzing ozone oxidation and degradation of organic matter.

[0240] In this embodiment, the initial concentration of oxalic acid is 100 mg / L, the volume is 200 ml; the ozone concentration is 5 mg / L, the flow rate is 0.5 L / min; and the reaction time is 15 min.

[0241] Example 6

[0242] Control experiments were carried out using the flexible catalysts prepared in Examples 1-5 and the two-dimensional metal catalyst prepared in Comparative Example 1, and ozone catalytic oxidation degradation experiments were carried out using oxalic acid as the target pollutant to examine the performance of the flexible layered catalyst and its optimal preparation conditions.

[0243] from Figure 8 It can be seen that the flexible layered catalysts with carriers containing flexible materials represented by silica gel prepared by Examples 1-3 of the present invention and the two-dimensional catalyst prepared by Comparative Example 1 carry out ozone catalytic oxidation degradation of oxalic acid experiments. When other conditions are the same, it can be clearly seen that the removal effect of the flexible layered catalyst is better than that of the two-dimensional catalyst. At 10 minutes, the removal rate of the flexible layered catalysts obtained in Examples 1, 2, and 3 can reach about 80%, while the two-dimensional catalyst can only reach 56%. At 15 minutes, the removal rates of the flexible layered catalysts obtained in Examples 1, 2, and 3 are 82.1%, 82.7%, and 81.7%, respectively, while the removal rate of the two-dimensional catalyst obtained in the comparative example is 65%. It can be seen that the removal rate and reaction rate of the flexible layered catalyst are further improved compared to the two-dimensional catalyst.

[0244] from Fig. 9 It can be seen that the flexible layered catalyst without channel 210 (for water flow) prepared in Example 4 of the present invention and the flexible layered catalyst with channel 210 prepared in Example 3 carried out ozone catalytic oxidation degradation of oxalic acid experiments. When other conditions are the same, the flexible layered catalyst without channel 210 prepared in Example 4 has a higher pollutant removal rate at the initial stage of the reaction than the flexible layered catalyst with channel 210 prepared in Example 3, but as the reaction time goes by, the pollutant removal rate of the flexible layered catalyst without channel 210 prepared in Example 4 shows a downward trend. This is because the flexible layered catalyst without channel 210 prepared in Example 4 has a larger surface area than the flexible layered catalyst with channel 210 prepared in Example 3, and thus has more catalytic active sites. Therefore, it shows a better removal effect at the initial stage of the reaction, but with the continuous impact of water inlet and aeration, such as Figure 7-2As shown, the flexible layered catalyst without channels 210 prepared in Example 4 is impacted by the water flow and accumulates, resulting in a decrease in the removal effect. In contrast, the flexible layered catalyst with channels 210 prepared in Example 3 is less impacted. Figure 7-1 As shown, it can be better suspended in water, so the removal effect is stable.

[0245] from Fig.10 It can be seen that the flexible layered catalyst without an activated carbon adsorption layer prepared in Example 5 of the present invention and the flexible layered catalyst with an activated carbon adsorption layer prepared in Example 3 carried out an ozone catalytic oxidation degradation of oxalic acid experiment. When other conditions are the same, it can be clearly seen that the removal effect of the flexible layered catalyst with an activated carbon adsorption layer prepared in Example 3 is better than that of the flexible layered catalyst without an activated carbon adsorption layer prepared in Example 5. After 15 minutes, the removal rate of pollutants by the flexible layered catalyst prepared in Example 3 can reach 81.7%, while the removal rate of pollutants by the flexible layered catalyst without an activated carbon adsorption layer prepared in Example 5 is only 75%. This shows that attaching a layer of activated carbon powder adsorption layer to the surface of the flexible sheet carrier has a great promoting effect on the catalytic effect. Fig.11 It can be seen that the flexible layered catalyst based on silica gel prepared by Examples 1 to 5 and the two-dimensional catalyst prepared by Comparative Example 1 of the present invention carry out ozone catalytic oxidation degradation of oxalic acid experiments. Under the same conditions, the recovery rate of the flexible layered catalyst is higher than that of the two-dimensional catalyst. After 15 minutes of reaction, the recovery masses of the flexible layered catalysts obtained in Examples 1 to 5 were 4.62g, 4.70g, 4.61g, 4.28g, and 4.78g, respectively, and the recovery rates were all about 90%. The recovery mass of the two-dimensional catalyst was 3.18g, and the recovery rate was only 64%. It can be seen that the flexible layered catalyst with a carrier of a flexible material represented by silica gel has better corrosion resistance, improves service life, and also avoids secondary pollution caused by metal loss.

[0246] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described with reference to the preferred embodiments of the present invention, it should be understood by those skilled in the art that various changes may be made in form and details without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A catalyst, characterized in that The catalyst comprises a carrier, and an active phase located on the carrier; The carrier has: a tensile strength in the range of 3.6 to 11.0 MPa, preferably a tensile strength in the range of 4.5 to 9.0 MPa; more preferably a tensile strength in the range of 6.0 to 8.0 MPa; The active phase comprises at least one metal oxide from Group VIII. Calculated by weight, the amount of the metal oxide from Group VIII accounts for 5% to 20% by weight of the total amount of the catalyst.

2. The catalyst according to claim 1, characterized in that The carrier comprises a flexible material, and the amount of the flexible material accounts for 80% to 95wt% of the total amount of the catalyst in terms of weight percentage; and / or, The flexible material is any one of silicone, polyvinyl chloride plastic, and rubber, or two or more thereof.

3. The catalyst according to claim 2, characterized in that The carrier has a tensile strength variation rate in the range of -15% to 15%; preferably, the carrier has a tensile strength variation rate in the range of -10% to 10%; further preferably, the carrier has a tensile strength variation rate in the range of -7% to 7%.

4. The catalyst according to claim 3, characterized in that The carrier is provided with a through channel; and / or, The carrier is a layered carrier, and a channel penetrating the thickness of the layered carrier is provided; and / or, The thickness H1 of the layered carrier is 200-800 μm.

5. The catalyst according to any one of claims 1 to 4, characterized in that The amount of the metal oxide from Group VIII accounts for 8% to 15 wt% of the total amount of the catalyst; preferably, the amount of the metal oxide from Group VIII accounts for 8% to 10 wt% of the total amount of the catalyst.

6. The catalyst according to claim 5, characterized in that The active phase comprises at least one metal oxide particle from Group VIII, the particles having a particle size D, the particle size D being not less than a thickness H1; and / or, The active phase also includes at least one adsorptive material.

7. A method for preparing a catalyst, characterized in that: The following steps are involved: preparing adsorbent material powder; preparing a liquid raw material, wherein the liquid raw material is a raw material for preparing the flexible material; preparing a metal oxide feedstock from Group VIII; Prepare catalyst curing and shaping mold; First, inject the adsorbent material powder into the bottom of the mold, Then, the liquid raw material and the metal oxide raw material are injected into the mold; Finally, spread the adsorbent material powder and solidify it.

8. The method for preparing the catalyst according to claim 7, characterized in that: The bottom of the mold is provided with a plurality of protrusions; the protrusions are used to form channels penetrating the thickness of the catalyst in the thickness direction.

9. The method for preparing a catalyst according to any one of claims 7 to 8, characterized in that: The flexible material is silicone. The liquid raw materials include: polydimethylsiloxane, methyl hydrogen silicone oil and silicone resin; Wherein, the mass ratio of the polydimethylsiloxane to the methyl hydrogen silicone oil is 100:(3-7); Calculated based on the sum of the masses of the polydimethylsiloxane and the methyl hydrogen silicone oil; The amount of the metal oxide raw material is 10wt% to 12wt% of the sum of the mass; The amount of the organic silicon resin is 10 wt % to 30 wt % of the sum of the mass.

10. The catalyst according to any one of claims 1 to 6, or the catalyst prepared by the method according to any one of claims 7 to 9, characterized in that: It is applied to catalytic oxidation for water treatment.